Drought - Detection and Solutions 2020
DOI: 10.5772/intechopen.86485
|View full text |Cite
|
Sign up to set email alerts
|

Native Plants to Arid Areas: A Genetic Reservoir for Drought-Tolerant Crops

Abstract: Droughts are common in arid areas. These cause important losses in crop production, while the increasing population demands more food and goods. Cultivars able to produce under drought conditions are required to avoid or reduce production losses. Plants have evolved different mechanisms to face drought, and many genes have been already discovered in model and cultivated plants that are involved in this trait. Some of these genes have been successfully transformed into cultivated plants for drought tolerance. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Once ABA binds to the ABI protein, the phosphate activity gets blocked by auto-phosphorylation and activation of OST1, a serine-threonine kinase in open stomata. OST1 and CDPK activate the ABA-responsive element-binding proteins (ABFs/AREBPs) and SLAC, respectively, under stress conditions [88]. GO annotation indicated that almost 57% of genes were involved in drought-related responses, of which ABA catabolic process, protein serine/threonine phosphatase complex, inositol 3-alpha-galactosyltransferase activity, and GTPase-binding activity were highly enriched.…”
Section: Expression Analysis Of Genes Under Drought Conditionmentioning
confidence: 99%
“…Once ABA binds to the ABI protein, the phosphate activity gets blocked by auto-phosphorylation and activation of OST1, a serine-threonine kinase in open stomata. OST1 and CDPK activate the ABA-responsive element-binding proteins (ABFs/AREBPs) and SLAC, respectively, under stress conditions [88]. GO annotation indicated that almost 57% of genes were involved in drought-related responses, of which ABA catabolic process, protein serine/threonine phosphatase complex, inositol 3-alpha-galactosyltransferase activity, and GTPase-binding activity were highly enriched.…”
Section: Expression Analysis Of Genes Under Drought Conditionmentioning
confidence: 99%
“…Arid to semiarid areas occupy at least 44% of the world land and these are responsible for nearly 38% of the global population [42][43][44]. These regions are climatically stressed by the limited rainfall, high temperatures and long dry seasons [45].…”
Section: Settingsmentioning
confidence: 99%